Outcomes after fixation of rib fractures sustained during cardiopulmonary resuscitation: A retrospective single center analysis - van Veelen, Nicole Maria; Buenter, Lea; Kremo, Valérie; Peek, Jesse; Leiser, Alfred; Kestenholz, Peter; Babst, Reto; Paulus Beeres, Frank Joseph; Minervini, Fabrizio (Frontiers in Surgery, 2023)
Background Historically rib fractures have been typically treated non-operatively. Recent studies showed promising results after osteosynthesis of rib fractures in trauma patients with flail segments or multiple rib fractures. However, there is a paucity of data on rib fixation after cardiopulmonary resuscitation (CPR). This study evaluated the outcomes of patients who received rib fixation after CPR. Methods Adult patients who received surgical fixation of rib fractures sustained during CPR between 2010 and 2020 were eligible for inclusion in this retrospective study. Outcome measures included complications, quality of life (EQ 5D 5L) and level of dyspnea. Results Nineteen patients were included with a mean age of 66.8 years. The mean number of fractured ribs was ten, seven patients additionally had a sternum fracture. Pneumonia occurred in 15 patients (74%), of which 13 were diagnosed preoperatively and 2 post-operatively. Six patients developed a postoperative pneumothorax, none of which required revision surgery. One patient showed persistent flail chest after rib fixation and required additional fixation of a concomitant sternum fracture. One infection of the surgical site of sternal plate occurred, while no further surgery related complications were reported. Mean EQ-5D-5L was 0.908 and the average EQ VAS was 80. One patient reported persisting dyspnea. Conclusion To date, this is the largest reported cohort of patients who received rib fixation for fractures sustained during CPR. No complications associated with rib fixation were reported whereas one infection after sternal fixation did occur. Current follow-up demonstrated a good long-term quality of life after fixation, warranting further studies on this topic. Deeper knowledge on this subject would be beneficial for a wide spectrum of physicians.